Teacher's Strategy in Improving Students Learning Motivation in Islamic Religious Education - Risyda Aini Khoerunnisa; N. Fathurrohman; Zaenal Arifin (Universitas Muhammadiyah Enrekang, 2021)
A motivational strategy in learning is a plan that includes a series of activities spescifically designed and developed to meet certain educational goals. Therefore, it is necessary to realize the goals of an ideal education plan in accordance with educational values. Therefore, teachers must have a learning motivation strategy to inspire students to learn in a fun, interesting and not monotonous way. To achieve the goal of increasing student motivation, teachers must increasingly choose and apply motivational teaching strategies, methods, and methods that are in accordance with these abilities. The purpose of this study is : a) Describing teachers strategies applied in increasing student motivation in Islamic Religious Education subjects. b) Describing the increase in students learning motivation in the subject of Islamic Religious Education. Keywords : Strategy, Learning Motivation, PAI Lessons. A motivational strategy in learning is a plan that includes a series of activities spescifically designed and developed to meet certain educational goals. Therefore, it is necessary to realize the goals of an ideal education plan in accordance with educational values. Therefore, teachers must have a learning motivation strategy to inspire students to learn in a fun, interesting and not monotonous way. To achieve the goal of increasing student motivation, teachers must increasingly choose and apply motivational teaching strategies, methods, and methods that are in accordance with these abilities. The purpose of this study is : a) Describing teachers strategies applied in increasing student motivation in Islamic Religious Education subjects. b) Describing the increase in students learning motivation in the subject of Islamic Religious Education. Keywords : Strategy, Learning Motivation, PAI Lessons.